The electron density of delocalized bonds (EDDB) applied for quantifying aromaticity. Issue 42 (24th October 2017) - Szczepanik, Dariusz W.; Andrzejak, Marcin; Dominikowska, Justyna; Pawełek, Barbara; Krygowski, Tadeusz M.; Szatylowicz, Halina; Solà, Miquel
Abstract : In this study the recently developed electron density of delocalized bonds (EDDB) is used to define a new measure of aromaticity in molecular rings. Abstract : In this study the recently developed electron density of delocalized bonds (EDDB) is used to define a new measure of aromaticity in molecular rings. The relationships between bond-length alternation, electron delocalization and diatropicity of the induced ring current are investigated for a test set of representative molecular rings by means of correlation and principal component analyses involving the most popular aromaticity descriptors based on structural, electronic, and magnetic criteria. Additionally, a qualitative comparison is made between EDDB and the magnetically induced ring-current density maps from the ipsocentric approach for a series of linear acenes. Special emphasis is given to the comparative study of the description of cyclic delocalization of electrons in a wide range of organic aromatics in terms of the kekulean multicenter index KMCI and the newly proposed EDDB k index.